PENGARUH STRATEGI PEMBELAJARAN INDEX CARD MATCH TERHADAP HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 003 PAGARAN TAPAH DARUSSALAM KECAMATAN PAGARAN TAPAH DARUSSALAM KABUPATEN ROKAN HULU - Nurzimah, Nurzimah; Alpusari, Mahmud; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem in this reasearch is that students are not directly involved and are not active in the learning process so students are not able to achieve maximum learning outcomes, so that it is improved by the Index Card Match learning strategy. This research aims to know the improvement of IPA learning outcomes of fifth grade students of SD Negeri 003 Pagaran Tapah Darussalam between before (pretest) and after (posttest) applying Index Card Match learning strategies. The research method used is an experiment with the research design of one group pretest-posttest. Science learning outcomes data were collected by the test technique in the form of objective tests. The results showed that there was an increase in science learning outcomes of the fifth grade students of SD Negeri 003 Pagaran Tapah Darussalam which were significant between the results before (pretest) and the results after (posttest) applying the Index Card Match learning strategy. This can be seen from the average initial test of 48.34 to 73.15 in the final test with an average increase of 0.50 including a moderate interpretation. Based on the results of data analysis, it can be concluded that the Index Card Match learning strategy has an effect on the science learning outcomes of fifth grade students of SD 003 Pagaran Tapah Darussalam.Key Words: Index Card Match learning strategy, science learning outcomes